Microencapsulation of ergosterol and Agaricus bisporus L. extracts by complex coacervation using whey protein and chitosan: Optimization study using response surface methodology. (April 2019) - Rudke, Adenilson Renato; Heleno, Sandrina A.; Fernandes, Isabel P.; Prieto, M.A.; Gonçalves, Odinei Hess; Rodrigues, Alírio E.; Ferreira, Isabel C.F.R.; Barreiro, Maria Filomena
Abstract: In the present work microencapsulation was applied to an ergosterol enriched extract (EEE) from Agaricus bisporus L. and pure ergosterol (PE) using a complex coacervation process. The process was optimized following two steps: (i) using response surface methodology to optimize the conditions of temperature ( T, 55 to 95 °C), protein-to-chitosan ratio ( P/C, 0.5 to 10.5), maximizing yield ( Y 1, %, w/w), efficiency ( Y 2, %, w/w) and load ( Y 3, %, w/w); and (ii) using the dose-response methodology to optimize the ergosterol content ( E ) at the optimal conditions achieved in (i). The global optimal conditions for both cases were the same ( T of 55 °C and a P/C of 0.5), but with maximized responses of Y 1 = 75.02%; Y 2 = 100.00%, Y 3 = 12.78%, and Y 1 = 19.19%; Y 2 = 100.00%, Y 3 = 15.87%, respectively. The effect of increasing ergosterol content led to the reduction of the microencapsulation yield, but with an increase in the ergosterol load and maintenance of the microencapsulation efficiency. Highlights: Complex coacervation as an efficient microencapsulation process for ergosterol. Whey protein and chitosan from industrial wastes used in the encapsulation process. Optimization of the coacervation process by Response Surface Methodology. Coacervates with high yield, encapsulation efficiency and ergosterol load. New functional ingredients compatible with food applications.